Investigating the Interplay of Live-In Relationships and Social Media: Effects on Perceptions, Dynamics, and Societal Changes (Indian Journal of Social Science and Literature (IJSSL), 2024)
This research paper delves into the intricate interplay between live-in relationships and the digital landscape of social media. The study explores how this interconnection influences various aspects of partnerships, including perceptions, dynamics, and broader societal changes. By examining the impact of social media on relationship formation,maintenance, and dissolution, as well as its role in shaping societal norms, the paper sheds light on the nuanced complexities that emerge in the modern era of digital connectivity.